PENGARUH MODA TRANSPORTASI BERBASIS APLIKASI TERHADAP PILIHAN MASYARAKAT DALAM MENENTUKAN MODA TRANSPORTASI DAN DAMPAKNYA TERHADAP PENDAPATAN DRIVER OJEK ONLINE - Sugiyarto Sugiyarto; Desilia Purnama Dewi; Edi Junaedi (Universitas Muhammadiyah Metro Lampung, 2020)
Changes in technology are very fast, ultimately making public transport business competition tougher and demanding the creativity of business actors. The presence of an application-based transportation mode has finally become the community's choice and shifts conventional transportation service providers. With a variety of conveniences including costs that are already known at the beginning of the order, making people feel comfortable with the services provided, then provides options for the public in using transportation services and provides income changes for online transportation-based motorcycle taxi drivers.This study aims to examine the direct impact of the presence of application-based modes of transportation that can change people's choices to switch from conventional modes of transportation to application-based modes of transportation and to determine the impact of changes in community choices on driver income. This research method uses quantitative methods, namely research methods based on the philosophy of positivism. The sampling technique was carried out randomly from the population. The data was collected by using a research instrument with a questionnaire distributed to respondents. This research uses path analysis test.Application-based mode of transportation (X) has a significant influence on people's choice in determining the mode of transportation (Y), is 27.1%, the remaining 72.9% is influenced by other variables. Variables X and Y have a significant effect on the income of online motorcycle taxi drivers (Z). While the coefficients (R Square) were 0.334 or 33.4%,this means that the influence of the application-based mode of transportation variable through the choice of the community in determining the mode of transportation on the income of online motorcycle taxi drivers is 33.4%, the remaining 66.6% is influenced by other variables not included in the study.The importance of upgrading technology so that the online motorcycle taxi application will further improve driver performance, increase consumer satisfaction and this mode of transportation is always the people's choice.Keywords: Mode of Transportation, Civil Preference, Driver's Income